The legal basis fot the application of patent waiver settlements in the COVID-19 pandemic - Christabel, Vania Rebecca (Economic Military and Geographically Business Review, 2024)
Background: The research on the role of the World Trade Organization (WTO) in solving the vaccine patent waiver problem related to the 2019 coronavirus disease pandemic will address each issue one by one. Seeing the waiver applications that were made from the end of 2020 to 2022, it is necessary to further study the legal basis and enforcement of patents. Coupled with its relation to public health and equality for the global world to achieve. This study aims to provide an understanding of the role of the WTO in the patent waiver application process and the continuity of current and future patent law enforcement. Method: This research is a normative research with a descriptive method that will explain with the aim of obtaining a description of the events of the patent waiver application. The data that has been obtained will be analysed qualitatively. Conclusions will be obtained from various descriptive data collected from primary and secondary sources that have been analysed. In this regard, this research will be descriptive-analytical in nature which will reveal existing regulations and their implementation. Findings: The results of this study are that the WTO has carried out its roles and functions in accordance with applicable international legal instruments. However, this research emphasises further on the principles of the WTO itself which emphasises justice for developing and less developed countries on the other words called Special and Differential Treatment of Developing Countries. Coupled with the existence of the Doha Declaration which should emphasise that public health should take precedence over intellectual property rights, including patents. Conclusion: Regarding the WTO's role in resolving vaccine patent issues during the COVID-19 pandemic, it can be concluded that the actions taken by the WTO, including its internal bodies and councils, adhere to applicable legal principles and the TRIPs Agreement. However, the decisions must fully align with the WTO's principles, particularly the Special and Differential Treatment of Developing Countries. Novelty/Originality of this study: This study analyzes the role of the WTO in resolving vaccine patent issues during the COVID-19 pandemic, focusing on the SDT principles and the Doha Declaration. It reveals the gap between international law and global health needs, offering a framework for balancing intellectual property rights with public health needs.